استراتيجيات التواصل مع الصم وضعاف السمع (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Article Presents A Humanitarian Issue For Many Researchers: Communication With The Deaf And The Visually Impaired, And The Philosophies On Which Communication Strategies Are Based.    Their Use Depends On The Degree Of Auditory Loss, And Therefore The Sense That Is Most Commonly Used In Learning Communicative Skill. Scientific And Studies Of The Following Communication Strategies: Key Words  -   Strategies , Communication  ,   The Deaf  , The Hard Of  Hearing,